Roles of platelets in tumor invasion and metastasis: A review. Issue 12 (December 2022) - Bian, Xiulan; Yin, Shengjie; Yang, Shuo; Jiang, Xinju; Wang, Jiaqi; Zhang, Minghui; Zhang, Lei
Abstract: The invasion and metastasis of malignant tumors are major causes of death. The most common metastases of cancer are lymphatic metastasis and hematogenous metastasis. Hematogenous metastasis often leads to rapid tumor dissemination. The mechanism of hematogenous metastasis of malignant tumors is very complex. Some experts have found that platelets play an important role in promoting tumor hematogenous metastasis. Platelets may be involved in many processes, such as promoting tumor cell survival, helping tumor cells escape immune surveillance, helping tumors attach to endothelial cells and penetrating capillaries for distant metastasis. However, recent studies have shown that platelets can also inhibit tumor metastasis. At present, the function of platelets in tumor progression has been widely studied, and they not only promote tumor cell metastasis, but also have an inhibitory effect. Therefore, in-depth and summary research of the molecular mechanism of platelets in tumor cell metastasis is of great significance for the screening and treatment of cancer patients. The following is a brief review of the role of platelets in the process of malignant tumor metastasis. Abstract : Platelets; Malignant tumors; Metastasis; Invasion.